2018
DOI: 10.3171/2018.7.focus18281
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities for effective data collection in global neurosurgery: traumatic brain injury surveillance experience in Malawi

Abstract: Global health research can transform clinical and surgical practice worldwide. Partnerships between US academic centers and hospitals in low- and middle-income counties can improve clinical care at the host institution hospital and give the visiting institution access to a large volume of valuable research data. Recognizing the value of these partnerships, the University of North Carolina (UNC) formed a partnership with Kamuzu Central Hospital (KCH) in Lilongwe, Malawi.The Department o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“…Within the pediatric TBI population at KCMC, we found a male-to-female ratio of about 2:1. Our findings are relatively consistent with the literature in Sub-Saharan Africa, which reports an average male-to-female ratio of 3:1 [ 29 34 ]. Males may be more prone to risky behaviors that lead to injuries possibly due to gender roles [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Within the pediatric TBI population at KCMC, we found a male-to-female ratio of about 2:1. Our findings are relatively consistent with the literature in Sub-Saharan Africa, which reports an average male-to-female ratio of 3:1 [ 29 34 ]. Males may be more prone to risky behaviors that lead to injuries possibly due to gender roles [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…RTI was by far the most common mechanism of injury, accounting for 64.4% of all patients in this study, which is comparable to global estimates. Reported percentages of RTI in children with TBI range from 48.3% in the Royal London Hospital to 53.3% in a Nigerian tertiary hospital and 60.7% in a tertiary center in Malawi [34,45]. One study estimating the global incidence of TBI found that the overall proportion of TBI resulting from road traffic crashes (RTCs) to be approximately 56% [10].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Barriers relating to both staffing and funding the trauma registry emerged as the first and second most common issues from respondents respectively, and is supported readily by papers that have documented or reported on their individual experience of trauma registry implementation [22][23][24][25][26] . A study by O'Reilly et al (2016), which reported the lessons learned of trauma registry development in both HICs and LMICs similarly identified both funding and staffing challenges as key topics to surface in their interviews with trauma registry custodians.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] For some trauma registries, government instability and a rotating cast of stakeholders within the respective Ministry of Health have made it challenging to disseminate their findings, especially if the value of injury surveillance research needs to be re-cultivated among the new cohort or if authorities only want results that confirm their administrative or political performance. [25][26][27] For other registries, especially those strongly driven by foreign collaborators, there is a possibility that publication in the scientific literature is given higher priority than efforts to disseminate results more locally. 25 28 The "publish or perish" paradigm retains a strong hold over many academic researchers that may, in some cases, overshadow efforts to disseminate the data with local stakeholders.…”
Section: Quality Of Trauma Carementioning
confidence: 99%